2017
DOI: 10.1038/s41598-017-05551-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Three Sheep Intestinal Regions reveals Key Pathways and Hub Regulatory Genes of Large Intestinal Lipid Metabolism

Abstract: The large intestine, also known as the hindgut, is an important part of the animal digestive system. Recent studies on digestive system development in ruminants have focused on the rumen and the small intestine, but the molecular mechanisms underlying sheep large intestine metabolism remain poorly understood. To identify genes related to intestinal metabolism and to reveal molecular regulation mechanisms, we sequenced and compared the transcriptomes of mucosal epithelial tissues among the cecum, proximal colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…The rumen and ileum are important organs for the digestion and absorption of nutrients in ruminants. The molecular mechanisms and key drivers underlying developmental changes in rumen and ileum in the early part of life have been revealed in several omics studies such as transcriptome analysis [ 54 , 55 ] and microbiome analysis [ 56 ]. In this study, we observed that 20.8% (33,107 genes) and 27.0% (4217) bovine genes were significantly DE between the pre-weaning (D33) and post-weaning (D96) periods in ileum and rumen tissues, respectively ( Figure 1 and Figure 2 , Supplementary Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rumen and ileum are important organs for the digestion and absorption of nutrients in ruminants. The molecular mechanisms and key drivers underlying developmental changes in rumen and ileum in the early part of life have been revealed in several omics studies such as transcriptome analysis [ 54 , 55 ] and microbiome analysis [ 56 ]. In this study, we observed that 20.8% (33,107 genes) and 27.0% (4217) bovine genes were significantly DE between the pre-weaning (D33) and post-weaning (D96) periods in ileum and rumen tissues, respectively ( Figure 1 and Figure 2 , Supplementary Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPT1A was the most DEG. CPT1A gene can catalyze the transfer of the acyl group of long-chain fatty acid-CoA conjugates to carnitine and plays an important role in triglyceride metabolism [ 2 , 14 ]. Up-regulation of CPT1A gene in intramuscular adipose from Jinhua pigs may play an important role in intramuscular adipose metabolism through the PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MBOAT1, which was enriched in glycerolipid metabolism pathway, also showed higher expression in the F line. MBOAT1 has been reported to be associated with phosphatidylcholine metabolism [46] and large intestine lipid metabolism [47]. An upregulation of MBOAT1 may, thus, also be associated with differences in IMF deposition between the two lines.…”
Section: Other Pathways Contribute To Increased Imf Deposition In F Linementioning
confidence: 99%